Research Progress of the Evaluation Technology of the Compatibility between Lubricating Oil and Transmission Synchronizer - Zhao Wei; Xu Wanli; Xu Ximeng; Su Bin (Jixie chuandong)
The lubricating oil plays an important role on the performance of transmission synchronizer,and the related compatibility evaluation can provide the technical support for reasonable selection oil.The domestic and overseas research progress of compatibility evaluation technology is summarized from test rigs,experimental parts and evaluation standards of experimental results.The similarity and difference between the experimental parts and simulative condition used in existing evaluation technology and the structure and actual condition used in domestic transmission synchronizer are discussed.Meanwhile,the research progress of lubricant performance evaluation used for manual transmission synchronizer is introduced.Finally,some challenging problems and developing trend of the related evaluation technology are pointed out.